El contexto de enseñanza un elemento fundamental en la implementación de innovaciones pedagógicas relacionadas con los Créditos Europeos - Masjuan, Josep M.; Elias, Marina; Troiano, Helena (Revista Complutense de Educación, 2009)
The aim of this paper is to show the results of a piece of research about attitudes, behaviours and assessments expressed by university students who participated in a pilot experience, about the process of European reform implementation. This pilot experience was focused in some innovations introduced in the teaching and learning process, related to ECTS, because the new curricula had not been still approved. The information has been collected at the end of six term courses whose students finalised the pilot experience (2007). This piece of research has been carried out at one university of Catalunya, autonomous region of Spain.
Keywords: European Higher Education Area; Evaluation by Students; Teaching and Learning at university; European Credit Transfer System (ECTS)